Optimizing the Search for Grass Supply for Garut Sheep Farmers Through Location-Based Mobile Application - Fawaz, Muhamad Fathur; Maulani, Galih Abdul Fatah; Hamdani, Nizar Alam (Entrepreneurship Faculty, Universitas Garut, 2023)
This research aims to address the challenges of finding grass supply for Domba Garut farmers. Information about the quantity and quality of grass supply is crucial for maintaining the health and productivity of the sheep. Developing Location Based Service (LBS) technology in Android is an important step as a solution to provide information about the location of grass supply and the types of grass needed by farmers. The information collected from monitoring and reporting grass supply through this Android application can assist farmers in planning, distribution, and ensuring a sustainable grass supply. The research results show that this application, based on UI/UX testing, received a very good rating, and the location-based features have a positive impact on efficiency in terms of time and search processes. As a result, the business processes lead to achieving an adequate amount of grass and contribute to the growth of the Domba Garut farming industry. Penelitian ini bertujuan untuk menjawab tantangan dalam mencari pasokan rumput bagi petani Domba Garut. Informasi tentang kuantitas dan kualitas pasokan rumput sangat penting untuk menjaga kesehatan dan produktivitas domba. Mengembangkan teknologi Location Based Service (LBS) di Android merupakan langkah penting sebagai solusi untuk memberikan informasi mengenai lokasi pasokan rumput dan jenis-jenis rumput yang dibutuhkan petani. Informasi yang dikumpulkan dari pemantauan dan pelaporan pasokan rumput melalui aplikasi Android ini dapat membantu petani dalam perencanaan, distribusi, dan memastikan pasokan rumput yang berkelanjutan. Hasil penelitian menunjukkan bahwa aplikasi ini, berdasarkan pengujian UI/UX, mendapatkan peringkat yang sangat baik, dan fitur berbasis lokasi berdampak positif pada efisiensi dalam hal waktu dan proses pencarian. Akibatnya, proses bisnis mengarah pada pencapaian jumlah rumput yang cukup dan berkontribusi pada pertumbuhan industri pertanian Domba Garut.